Répercussions actuelles et futures du changement climatique sur les communautés benthiques dans l'Arctique Canadien - Pierrejean, Marie (Université Laval, 2020)
The Arctic Ocean is emerging as one of the regions that is most affected by climate change. A significant increase in precipitation and sea surface water temperatures are expected and will undeniably lead to a significant loss of sea ice cover. Because of their effects on physicochemical parameters, these changes are expected to directly impact the surface primary producers (sea ice algae and phytoplankton), thereby limiting organic matter input towards the seafloor. It is thus commonly accepted that climate change will affect the distribution, diversity and abundance of benthic communities, due to its impact on environmental parameters (pelagic-benthic coupling and physicochemical parameters), and on ecosystem services and functions (e.g., benthic remineralization). As a consequence, the decrease in sea ice cover, the desalination of the surface layer or the increase in shipping traffic in the Hudson Bay Complex and in the eastern Canadian Arctic will likely lead to major changes in benthic community structure and biogenic structural habitats. In this context and since the impacts of climate change on benthic arctic ecosystems were still poorly understood, the objectives of this thesis were to i) describe the diversity and distribution of epibenthic communities in the Hudson Bay Complex and ii) understand the effects of climate change on biodiversity and benthic ecosystem functioning. The outcomes of this thesis allowed us to i) provide the most recent survey on epibenthic organisms in the Hudson Bay Complex and their relationships with environmental variables; ii) identify diversity hotspots sensitive to climate change; and iii) document and compare benthic biodiversity and fluxes within biogenic structures and adjacent bare sediments in the Canadian Arctic. A total of 380 taxa have been identified from 46 stations sampled across the Hudson Bay Complex. Despite the relatively low spatial coverage of our sampling, we estimated that our survey represented 71% of the taxa present in the Hudson Bay Complex. We ...